The Concept of Slum Management Become A Tourism Zone In Kendari City - Brata, Joko Tri (UI Scholars Hub, 2023)
This study aims to assess to find out how the public views the handling of slums in the Kendari City Coastal Area and how the sustainability of slum handling. This research is classified as a qualitative research type, by analyzing the area to be studied because this research is classified as an exploratory research type, by describing the condition and situation of the area that is the object of research. To answer the first research objective related to the pattern of slum handlers, a survey was conducted to find out the pattern of handling slums in Kendari City, carried out by analyzing data sourced from literature and reports on the results of treatment. and for the second problem an analysis will be carried out on the next plan for handling slums. In this case the researcher will conduct a qualitative analysis, by describing based on the documentation materials of the results of the research. The results of the study show that sustainability by the community is carried out by the community beneficiaries of the program, with the existence of a Planning Document made by the Community through BKM which aims to make the implementation of Slum Management sustainable. Analysis of the impact received by the community by comparing the conditions of the settlements before and after the implementation of the slum management program based on the determinants of the criteria (physical and non-physical) and the established indicators obtained an illustration that the community received a significant impact. Analysis of increasing knowledge, even though the nuances of the project are very thick, but the principles of measurable empowerment with predetermined achievements are carried out in accordance with existing regulations, so that clashes of thought between empowerment goals versus project goals can be minimized and Community capacity building analysis can be it was found that increasing community capacity was described by the preparation of a Settlement Environmental Management Plan (RPLP) document which was compiled as a guideline based on the aspirations, needs and ideals of the community to improve the environmental conditions of their settlements. In particular, the results of this study illustrate that in an effort to turn slum areas into tourist areas, the pattern of handling slums is shown by emphasizing the need for an intensive program in handling slums in Kendari City, in an integrated, comprehensive and holistic way, namely: Integrated pattern of handling, which is integrated by applying the concept of community-based development (CBD) development, Redevelopment, Revitalization (physical, environmental, social, economic, cultural), as well as efforts to apply the principles of Urban Sustainable Development, so that slum areas can maintain their environment and at the same time have economic value tourist area.